Improving health care communication for caregivers: A pilot study. Issue 4 (2nd October 2018) - Smith, Paul D.; Martin, Beth; Chewning, Betty; Hafez, Stephanie; Leege, Erin; Renken, Jill; Smedley Ramos, Rachel
ABSTRACT: With the growing older adult population, there will also be more informal caregivers assisting friends and family with their health care. With the increasing complexity of health care, improved caregiver communication skills have the potential to reduce caregiver burden and frustration and improve care recipient health. The primary goal of this project was to develop and refine the content and teaching methods of a small-group behavioral change program to improve communication between caregivers of older adults and health care professionals. The authors developed the Care Talks program for improving communication between caregivers and health care professionals. They conducted a prospective cohort feasibility study of the intervention to assess caregiver communication confidence at baseline and one month postintervention. Six participants were enrolled. Of the 15 participants who answered the question, 15 (100%) would recommend this program to a friend. There was significant improvement in a 10-question composite of communication confidence pre/post scores from 74.1 to 79.6 p = .03. This small-group behavioral change intervention significantly improved communication confidence for this sample of caregivers. Further research is needed to determine the long-term effects of this program on caregivers and care recipients.